Effects of interstimulus intervals on behavioral, heart rate, and event‐related potential indices of infant engagement and sustained attention. (9th May 2016) - Xie, Wanze; Richards, John E.
Abstract: Maximizing infant attention to stimulus presentation during an EEG or ERP experiment is important for making valid inferences about the neural correlates of infant cognition. The present study examined the effects of stimulus presentation interstimulus interval (ISI) on behavioral and physiological indices of infant attention including infants' fixation to visual presentation, the amount of heart rate (HR) change during sustained attention, and ERP components. This study compared an ISI that is typically used in infant EEG/ERP studies (e.g., 1, 500–2, 000 ms) with two shorter durations (400–600 ms and 600–1, 000 ms). Thirty‐six infants were tested cross‐sectionally at 3, 4.5, and 6 months. It was found that using the short (400–600 ms) and medium (600–1, 000 ms) ISIs resulted in more visually fixated trials and reduced frequency of fixation disengagement per experimental block. We also found larger HR changes during sustained attention to both of the shorter ISIs compared with the long ISI, and larger ERP responses when using the medium ISI compared to using the short and long ISIs. These data suggest that utilizing an optimal ISI (e.g., 600–1, 000 ms), which increases the presentation complexity and provides sufficient time for information processing, can promote infant engagement and sustained attention during stimulus presentation.